2021
DOI: 10.5014/ajot.2021.045336
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Modifications and Supports for Participation Among Adults Aging With Intellectual and Developmental Disabilities: A Scoping Review

Abstract: Importance: Adults aging with intellectual and developmental disabilities (IDD) continue to face barriers to participation in meaningful occupation; moreover, the increased life expectancy of adults with IDD intensifies the need for age- and environment-specific support. Objective: To map and categorize transdisciplinary literature on environmental modifications and supports for adults aging with IDD. Data Sources: Studies published between January 1, 2000, and January 1, 2019, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In recent years, increased attention has been given to models that support a person to continue living in their preferred living environment, often known as “aging in place.” Washington et al (2021) concluded that occupational therapists have an important role in supporting adults aging with ID to age in place. In Ireland, this is reflected in policies such as the National Positive Aging Strategy (Department of Health, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, increased attention has been given to models that support a person to continue living in their preferred living environment, often known as “aging in place.” Washington et al (2021) concluded that occupational therapists have an important role in supporting adults aging with ID to age in place. In Ireland, this is reflected in policies such as the National Positive Aging Strategy (Department of Health, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics in this study showed many people aging with ID don't have friends outside of their home, and require support for ADL. Washington et al (2021) reported there are opportunities for occupational therapists to work with adults aging with ID to focus on developing friendships in and outside the home, and supporting participation within the community. Leisure activities are a valuable way to maintain and expand social networks through participation in occupation within communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical theories used in research turn the gaze from the individual to society, thereby illuminating social structures that "maintain a status quo of power" (Scotland, 2012, p. 13). Studies in this special issue take a critical approach that interrogates broadly accepted concepts or practices in the field or acknowledges power structures, such as ableism and sanism, that oppress disabled people (Bathje et al, 2021;Holler et al, 2021;Magasi et al, 2021;McArthur & Gill, 2021;Rabaey et al, 2021;Sheth et al, 2021;VanPuymbrouck et al, 2021;Washington et al, 2021).…”
Section: Researchmentioning
confidence: 99%
“…Implications for occupational therapy outlined across the articles in this special issue call on the profession and individual practitioners to engage in advocacy. The authors recommend facilitating the development of client selfadvocacy (Bathje et al, 2021;Rabaey et al, 2021;Stasell & Bathje, 2021), collaborating with and referring to programs and organizations that support community participation and occupational justice (Bathje et al, 2021;Sheth et al, 2021;Wasmuth et al, 2021), and advocating for disability benefits, accessible community and health care services, and equitable policies (McArthur & Gill, 2021;Njelesani et al, 2021;Stasell & Bathje, 2021;VanPuymbrouck et al, 2021;Washington et al, 2021). In addition, some authors call for the profession and its educators, researchers, practitioners, and students to confront implicit bias (Friedman & VanPuymbrouck, 2021) and power dynamics (Magasi et al, 2021) to more authentically infuse DS priorities into practice.…”
Section: Advocacymentioning
confidence: 99%